Do ‘New’ Multinationals Behave Differently from ‘Old’ Multinationals? --- An Examination of Internationalization of Sinopec Group and Royal Dutch Shell - SHEN, JIAMIN (2011)
Internationalization of firms has become a prominent phenomenon following the ever deepening process of economic globalization. The emergence of new multinational enterprises (MNEs) in particular has significantly reshaped the international business landscape and thus has attracted increasing attention of scholars, practitioners and policy makers. Employing a theoretical framework that integrates resource-based view, institutional-based view, and industry-based view, this dissertation aims to discover the distinctive internationalization behaviour of new MNEs in the context of conventional MNEs. More specifically, the dissertation examines the differences in internationalization behaviour between ‘new’ and ‘old’ MNEs with respect to internationalization speed, international expansion path and entry mode choices. The study employs case study approach and uses Royal Dutch Shell and Sinopec Group as examples.